Induction of a potent immune response in the elderly using the TLR-5 agonist, flagellin, with a recombinant hemagglutinin influenza–flagellin fusion vaccine (VAX125, STF2.HA1 SI) - Taylor, David N.; Treanor, John J.; Strout, Cynthia; Johnson, Casey; Fitzgerald, Theresa; Kavita, Uma; Ozer, Karen; Tussey, Lynda; Shaw, Alan (Vaccine, 2011)
Influenza vaccines perform poorly in the elderly with reduced serological response and vaccine efficacy. We evaluated a novel influenza vaccine consisting of the globular head of the HA1 domain of the A/Solomon Islands/3/2006 (H1N1) influenza virus (VAX125) genetically fused to the TLR5 ligand, flagellin, and produced in Escherichia coli. 120 subjects ≥65 years old were enrolled at three clinical centers. VAX125 vaccine was administered at doses of 0.5, 1, 2, 3, 5 or 8μg delivered i.m. as a single dose vaccination on Day 0 using a dose-escalation with 20 subjects in each dose level. Subjects were followed for adverse events and sera were tested by hemagglutination-inhibition (HAI) against egg-grown virus on days 0, 7, 14, and 28. Serum C-reactive protein (CRP) and anti-flagellin antibody were also assessed. The mean age was 71 years. The vaccine was well tolerated at all dose levels, with no more than mild to moderate local or systemic symptoms. The geometric mean titers (GMT) increased in all dose groups. In the 5μg group the day 14 post-vaccination HAI titer was 1:226 showing a 12-fold increase over baseline. The 8μg group showed a similar post-vaccination GMT increase (∼8-fold). In the combined 5 and 8μg groups, the seroconversion rate was 75% and the seroprotection rate was 98%. A 5μg dose of VAX125 was safe and able to induce a greater than 10-fold increase HAI antibody levels and nearly complete seroprotection in subjects over 65 years old. The use of flagellin to adjuvant influenza vaccines via the TLR5 innate immune pathway appears to be a useful approach to overcome poor immune responses in the elderly. VAX125 is a promising new candidate for prevention of influenza A disease in both young adults and the elderly.